Mandibular second molar root canal morphology and variants in a Korean subpopulation - Kim, S. Y.; Kim, B. S.; Kim, Y. (International endodontic journal, 2016)
Aim To determine the root canal anatomy of mandibular second molars in a Korean population by analysing cone‐beam computed tomography (CBCT) images. Methodology The CBCT images of 960 subjects were examined. The number and configuration of roots and canals were categorized according to Vertucci's and modified Melton's classifications. Results Of the 1920 mandibular second molars, 41% had one root, 58% had two roots, and <1% had three roots. In the mesial roots of two‐rooted molars, Vertucci's Type lV (44%) and Type II (37.75%) canals were most frequent. The prevalence of C‐shaped roots was 40%, and C‐shaped roots in combination with additional mesiolingual or distolingual roots were found in <1% of molars. Interestingly, O‐shaped canals were detected in 0.10% of the molars. Of the C‐shaped roots, the most common configuration types were Melton's Type I (66%) in the coronal region and Melton's Type III (56%) in the apical region. The prevalence of C‐shaped roots was higher in females (47%) than in males (32%) (P < 0.001) and did not differ with age (P = 0.497) or tooth position (P = 0.514). Most (82%) C‐shaped canals were bilateral (P < 0.001). Conclusions A high prevalence of C‐shaped canals and a low incidence of three‐rooted molars were observed in the mandibular second molars of the Korean subpopulation studied.